2015
DOI: 10.1104/pp.15.01003
|View full text |Cite
|
Sign up to set email alerts
|

GLYCOLATE OXIDASE3, a Glycolate Oxidase Homolog of Yeast l-Lactate Cytochrome c Oxidoreductase, Supports l-Lactate Oxidation in Roots of Arabidopsis

Abstract: In roots of Arabidopsis (Arabidopsis thaliana), L-lactate is generated by the reduction of pyruvate via L-lactate dehydrogenase, but this enzyme does not efficiently catalyze the reverse reaction. Here, we identify the Arabidopsis glycolate oxidase (GOX) paralogs GOX1, GOX2, and GOX3 as putative L-lactate-metabolizing enzymes based on their homology to CYB2, the L-lactate cytochrome c oxidoreductase from the yeast Saccharomyces cerevisiae. We found that GOX3 uses L-lactate with a similar efficiency to glycolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 75 publications
3
46
0
Order By: Relevance
“…Our genetic analysis indicated that the lack of GOX3, HAOX1, and HAOX2 does not influence the photorespiratory phenotype of cat2-2, which is in line with their substrate preferences and tissue-specific expression (Hodges et al, 2013;Esser et al, 2014;Engqvist et al, 2015). GOX1 and GOX2, on the other hand, metabolize glycolate in vitro with similar kinetic parameters and have been assumed to equally support the photorespiratory pathway.…”
Section: Lack Of Gox1 But Not Gox2 Attenuates the Photorespiratory mentioning
confidence: 72%
See 2 more Smart Citations
“…Our genetic analysis indicated that the lack of GOX3, HAOX1, and HAOX2 does not influence the photorespiratory phenotype of cat2-2, which is in line with their substrate preferences and tissue-specific expression (Hodges et al, 2013;Esser et al, 2014;Engqvist et al, 2015). GOX1 and GOX2, on the other hand, metabolize glycolate in vitro with similar kinetic parameters and have been assumed to equally support the photorespiratory pathway.…”
Section: Lack Of Gox1 But Not Gox2 Attenuates the Photorespiratory mentioning
confidence: 72%
“…S7). Similarly, the lack of GOX3, which is predominantly expressed in roots and senescing leaves and uses glycolate and L-lactate with comparable efficiency (Engqvist et al, 2015), did not reduce the GOX activity (Supplemental Fig. S7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using dynamic light conditions that mimic the natural environment more closely, this study was able to reveal photosynthetic deficiencies in some peroxisomal mutants, such as gox1 (glycolate oxidase 1) and pxn1 (peroxisomal NAD + transporter), which otherwise show no apparent phenotypes in constant laboratory light conditions, suggesting the importance of these peroxisomal proteins in photosynthetic performance under high/ dynamic light conditions. Mutant and gene expression analyses in Arabidopsis showed that GOX1 and GOX2 function in photorespiration, whereas GOX3 is more involved in metabolizing l-lactate to sustain low concentrations of l-lactate in roots (Engqvist et al, 2015), and HAOX1 and HAOX2 are highly expressed in seeds (reviewed in Dellero et al, 2016). Li et al, 2019b).…”
Section: Photorespirationmentioning
confidence: 99%
“…Enzymatic activity was assayed spectrophotometrically according to Engqvist et al (2015) using a Synergy HT Plate reader with Gen5 Analysis software (Biotek). The standard oxidase assay mixture consisted of 100 mM 3-Morpholinopropane-1-sulfonic acid (MOPS-NaOH, pH 7.0) or Tris-HCl (pH 8.5) containing 0.5 mM EDTA, 5 mM MgSO 4 , 4 mM phenylhydrazin, and either 2 mM FAD or 2 mM FMN as cofactors.…”
Section: Enzymatic Activity Assaysmentioning
confidence: 99%